2019
DOI: 10.1080/14789949.2019.1581831
|View full text |Cite
|
Sign up to set email alerts
|

Single-item predictive validity of the Short-Term Assessment of Risk and Treatability (START) for violent behaviour in outpatient forensic psychiatry

Abstract: The single-item predictive validity of the Short-Term Assessment of Risk and Treatability (START) has not been thoroughly investigated, although this has great clinical relevance for the selection of treatment targets. Furthermore, it remains unclear whether the characteristic START additions of scoring strengths next to vulnerabilities and selecting key items, add incremental predictive validity. Finally, predictive validity has primarily been studied in inpatient settings and included mainly patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Most studies of predictive validity test the association of the total scores on the two START scales with violent outcomes but some more concise variations of the START have also been tested in this way including the accuracy of individual items (O'Shea & Dickens, 2015;Paetsch et al, 2019). In particular, Braithwaite et al (2010) examined the predictive validity of the overall START (all twenty items) and compared this overall predictive validity with that for various shortened "optimized scales" related to violence and the other outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of predictive validity test the association of the total scores on the two START scales with violent outcomes but some more concise variations of the START have also been tested in this way including the accuracy of individual items (O'Shea & Dickens, 2015;Paetsch et al, 2019). In particular, Braithwaite et al (2010) examined the predictive validity of the overall START (all twenty items) and compared this overall predictive validity with that for various shortened "optimized scales" related to violence and the other outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This outcomes (Paetsch et al, 2019). It is also of note that this may uniquely reflect the perceptions of the Thai mental health professionals.…”
Section: Discussionmentioning
confidence: 82%
“…The significant structural relationships between two START subscales may suggest a construct validity (Atkinson et al, 2011;Tavakol & Wetzel, 2020), which it has so far not been considered and examined. Several researchers and clinicians have supported the increment validity of the START for incorporating the strength subscale into the risk assessment framework (Braithwaite et al, 2010;Desmarais et al, 2012;O'Shea, Picchioni, & Dickens, 2016;Paetsch, van Os, Troquete, & van den Brink, 2019). The concept of incorporating the protective factor or the START strength subscale is debated at a fundamental level in terms of whether it is a unique entity or is simply the reverse of a risk factor or START vulnerability subscale (Haines et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kikuchi et al [16] found START being a feasible and valid tool that allows staf to plan treatment and promote the recovery of forensic patients. Te predictive validity of START varies considerably; for instance, Paetsch [17] revealed that only fve of the START items had predictive validity for the occurrence of violence in the following six months. Terefore, the potential limitations of START in capturing the full range of outcomes should be carefully considered, and it should not be solely relied upon.…”
Section: Structured Assessment Model Of the Risksmentioning
confidence: 99%